Intramuscular Anatomy Drives Collagen Content Variation Within and Between Muscles - Binder-Markey, Benjamin I.; Broda, Nicole M.; Lieber, Richard L. (Frontiers in Physiology, 2020)
The passive load bearing properties of muscle are poorly understood partly due to challenges in identifying the connective tissue structures that bear loads. Prior attempts to correlate passive mechanical properties with collagen content (often expressed as a mass ratio and used as a surrogate for connective tissue quantity within muscle) have not been successful. This is likely a result of not accounting for variability in intramuscular connective tissue throughout a muscle such that a single collagen content value likely does not adequately represent the connective tissue load bearing capacity of a muscle. Therefore, the purpose of this study was to determine how intramuscular connective tissue distribution throughout a muscle impacts measured collagen content. For this analysis, four mouse hindlimb muscles were chosen because of their varying actions and anatomy; rectus femoris, semimembranosus, tibialis anterior, and lateral gastrocnemius. Collagen content throughout each muscle was determined biochemically using an optimized hydroxyproline assay. Dense connective tissue distribution throughout each muscle’s length was quantified histologically. We found that collagen content varied widely within and between muscles, from 3.6 ±0.40 SEM μg/mg wet weight to 15.6 ±1.58 SEM μg/mg, which is dependent on both the specific location within a muscle and particular muscle studied. Both collagen content and connective tissue structures demonstrated stereotypically patterns with the highest quantity at the proximal and distal ends of the muscles. Additionally, using three independent approaches, (1) linear regression, (2) predictive modeling, and (3) nonlinear optimization, we found complementary and corroborating evidence suggesting a strongly correlated relationship between a muscle’s connective tissue distribution and collagen content. Specifically, we found that muscle collagen content is driven primarily by its dense connective tissue structures due to the extremely high collagen content of connective tissue (227.52 to 334.69 μg/mg) compared to muscle tissue (1.93 to 4.03 μg/mg). A consequence of these findings is that a single collagen content measurement does not accurately represent a muscle’s complex distribution of connective tissue. Future studies should account for collagen content variations and connective tissue anatomy to establish more accurate relationships between collagen content measurements and whole muscle passive mechanics.